2016
DOI: 10.1111/1742-6723.12582
|View full text |Cite
|
Sign up to set email alerts
|

Trends and characteristics of short‐term and frequent representations to emergency departments: A population‐based study from New South Wales, Australia

Abstract: In this population-based study, short-term representations were highest in the infant patient population, in-patient readmission rates were highest in the elderly and very frequent representations to ED were characterised by middle-aged patients with mental health or drug and alcohol related presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 16 publications
4
25
0
Order By: Relevance
“…), and those with AOD misuse and mental illness are most likely to become very frequent (>30 presentations/year) presenters to the ED (Dinh et al . ). Although there did not appear to be a difference in the re‐presentation rate between the cohorts in the present study, other work has shown that screening, brief intervention, referral, and treatment (SBIRT) in the ED have reduced the harmful use of AOD in this population (Cherpitel et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), and those with AOD misuse and mental illness are most likely to become very frequent (>30 presentations/year) presenters to the ED (Dinh et al . ). Although there did not appear to be a difference in the re‐presentation rate between the cohorts in the present study, other work has shown that screening, brief intervention, referral, and treatment (SBIRT) in the ED have reduced the harmful use of AOD in this population (Cherpitel et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, we hypothesized that patients presenting involuntarily with or without an AOD issue might in itself be a risk factor for re-presentation to the ED. Previous work in Australia has shown that re-admissions are highest when patients have unmet psychosocial needs upon leaving the department (Moore et al 2012), and those with AOD misuse and mental illness are most likely to become very frequent (>30 presentations/year) presenters to the ED (Dinh et al 2016). Although there did not appear to be a difference in the re-presentation rate between the cohorts in the present study, other work has shown that screening, brief intervention, referral, and treatment (SBIRT) in the ED have reduced the harmful use of AOD in this population (Cherpitel et al 2009;Cunningham et al 2009;D'Onofrio et al 2012;Daeppen et al 2007;D esy & Perhats 2008;InSight Project Research Group 2009;Madras et al 2009;Woodruff et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, the rates of ED re‐presentations within 72 h range between 1% and 5% . In Australia, one New South Wales (NSW) population study and one single centre study from Sydney both demonstrated a re‐presentation rate of 4.9% . This local rate is at the higher end of the range compared to international studies and may represent a greater burden.…”
Section: Introductionmentioning
confidence: 97%
“…The rate of 72 h ED re‐presentations is used as a key performance indicator and is often regarded as a measure of the quality of care provided to patients along with the presence and adequacy of follow‐up healthcare options . Information about these 72 h re‐presentations allows for comparison between healthcare districts with regards to differences in ED use and access to additional primary or specialised care …”
Section: Introductionmentioning
confidence: 99%
“…Despite these complexities, management of the frail older adult continues to be caught up in the ‘one size fits all’ model of care currently seen in many EDs . This often leads to unnecessary invasive investigations, high rates of admission and re‐admission, delayed and fragmented care and longer ED LoS . If admitted, RACF residents suffer high rates of iatrogenic hospital acquired complications such as falls, urosepsis and delirium .…”
Section: Introductionmentioning
confidence: 99%